On the Diminishing Returns of Higher-order Terms in Asymptotic Expansions of Bias - Maurice J.G. Bun; Jan F. Kiviet (Tinbergen Institute, 2002)
The relative magnitudes are compared of successive terms in a higher-order asymptotic expansion of the bias of the LSDV estimator in dynamic panels. We find that the leading term accounts for the major part of the actual bias in small samples. This implies that bias correction procedures can be based on relatively simple bias approximation formulas.
Keywords: C13; C23; 330; Mymptotic expansion; biM approximation; dynamic panel data model; finite sample biM; LSDV estimator; Bias; Panelforschung; Theorie